Mental Well-being on Grit and Spiritual Intelligence - Laila Azizah Hakim; Ratna Sari (Universitas Pendidikan Ganesha, 2025)
In 2022, the Indonesian National Adolescent Mental Health Survey (I-NAMHS) reported that 34.9% of Indonesian adolescents experienced mental health issues. Several studies have found that students are vulnerable to experiencing psychological disorders up to depressive disorders. According to pre-research findings, some students lost interest in their academic because they felt pushed by academic tasks, but they did not believe that their spiritual lives were suffering. This phenomenon show that academic pressures not only impact adolescents but also university students, highlighting the academic complexities that impact their mental health. This study aims to determine the influence of grit and spiritual intelligence on the mental well-being of students from the Faculty of Islamic Studies at Muhammadiyah University of Yogyakarta, batch 2022. The respondents in this study consisted of 75 students. This study uses a quantitative approach employing the multiple linear regression analysis. The data collection technique was carried out using a questionnaire accessed through the Google Form website. The results show that the sig. value of 0.000 < 0.05 means that grit and spiritual intelligence have an impact on mental well-being. The variables of grit and spiritual intelligence contribute to mental well-being by 50.3% and are influenced by other variables by 49.7%. The research results indicate that the students of the Faculty of Islamic Studies, Muhammadiyah University Yogyakarta batch 2022 have high levels of grit, spiritual intelligence, and mental well-being. Therefore, students with high levels of grit and spiritual intelligence tend to have better mental well-being.